Optimization models for the cost-effective design and operation of renewable-integrated energy systems - Kim, Jin-Kuk; Park, Haryn; Kim, Se-jung; Lee, Joohwa; Song, Yongjae; Yi, Sung Chul (Renewable & sustainable energy reviews, 2023)
Novel and simple optimization methods have been developed for the cost-effective design and operation of domestic and commercial energy systems when energy consumers have access to renewable energy. The new optimization framework is formulated such that time-dependent variations in energy demand and renewable energy availability are accommodated, while unnecessary non-linearity and computational complexities are avoided. The simplicity in the optimization model with a proposed solution strategy enables the use of a spreadsheet-based solver that adequately encapsulates the impact of renewable energy integration on fossil fuel-based energy generation and predicts economic sizes of energy storage units. The developed optimization model also allows economic trade-offs between capital investment and operation costs, which determines the cost-effective operational profiles of energy supplies and its exchange through energy storage. To demonstrate the applicability and effectiveness of the proposed optimization models, case studies are conducted to identify the most cost-effective energy generation and utilization of renewable energy through a storage unit for different levels of renewable energy use; for example, up to 40% and 20% wind and solar energy contributions, respectively, are considered for summer and winter subject to constraints on the capacity or heat-to-power ratio of conventional energy generators. [Display omitted] •The study presents a new optimization model for renewable-integrated energy systems.•Optimal sizing and design of energy storage is important for renewable integration.•Design complexities are effectively dealt with the optimization model proposed.